KEMAMPUAN KONEKSI MATEMATIS SISWA DENGAN MENGGUNAKAN PENDEKATAN MATEMATIKA REALISTIK - Nurullita Astriani; Muhammad Bayu Al Dhana; Lola Zeramenda Br Tarigan; Nayla Aiwina Putri (Al-Irsyad Journal of Mathematics Education, 2025)
ABSTRACT Mathematical connection ability is one of the most important abilities because it will help mastery of meaningful conceptual understanding and help complete problem-solving tasks through the relationship between mathematical concepts and between mathematical concepts and concepts in other disciplines. With a realistic mathematical approach, it is seen as being able to provide learning that will have a good impact on students’ mathematical connection abilities because in learning it will be linked to the real world which is used as a basis for understanding mathematical concepts so that students understand the benefits of mathematics. The purpose of this research aims to analyze students’ mathematical connection abilities using a realistic mathematical approach. This study is a Quasi Experiment study. The population of this study was all students of class VIII of SMP Negeri 1 Pangkalan Susu. The research sample was taken from two classes, namely class VIII-1 and VIII-2 with the Simple Random Sampling Technique. The instrument of this study was a test, namely to measure mathematical connection abilities. Data analysis of students’ mathematical connection ability test results in the form of descriptive data analysis, normality tests, homogeneity tests and hypothesis tests. The results showed that the mathematical connection abilities of students who were given learning with a realistic mathematical approach were better than the mathematical connection abilities of students who were given conventional learning. Keywords : Mathematical Connection Ability; Realistic Mathematics Approach ABSTRAK Kemampuan koneksi matematis merupakan salah satu kemampuan yang sangat penting dikarenakan akan membantu penguasaan pemahaman konsep yang bermakna dan membantu menyelesaikan tugas pemecahan masalah melalui keterkaitan antar konsep matematika dan antara konsep matematika dengan konsep dalam disiplin lain. Dengan pendekatan matematika realistik dipandang dapat memberikan pembelajaran yang akan membawa dampak baik terhadap kemampuan koneksi matematis siswa karena di dalam pembelajaran akan dikaitkan dengan dunia nyata yang digunakan sebagai dasar di dalam memahami konsep matematika sehingga siswa memahami manfaat dari matematika tersebut. Tujuan dari penelitian ini bertujuan untuk menganalisis kemampuan koneksi matematis siswa dengan menggunakan pendekatan matematika realistik. Penelitian ini merupakan penelitian Quasi Experiment. Populasi penelitian ini adalah seluruh siswa kelas VIII SMP Negeri 1 Pangkalan Susu. Sampel penelitian diambil dua kelas yaitu kelas VIII-1 dan VIII-2 dengan Teknik Simple Random Sampling. Instrumen penelitian ini adalah tes yaitu untuk mengukur kemampuan koneksi matematis. Analisis data hasil tes kemampuan koneksi matematis siswa berupa analisis deskriptif data, uji normalitas, uji homogenitas dan uji hipotesis. Hasil penelitian menunjukkan bahwa kemampuan koneksi matematis siswa yang diberi pembelajaran dengan pendekatan matematika realistik lebih baik dari pada kemampuan koneksi matematis siswa yang diberi pembelajaran konvensional. Kata kunci: Kemampuan Koneksi Matematis; Pendekatan Matematika Realistik.